PANDANGAN MASYARAKAT UMUM TERHADAP PERWAKILAN WALI DALAM AKAD NIKAH (STUDI DI DESA TOBOINO HALMAHERA TIMUR MALUKU UTARA) - Tifri Saputri; Musyaffa Musyaffa (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The implementation of marriage requires the fulfillment of the conditions and basic pillars. One of the pillars of marriage is the marriage guardian. Basically, the obligatory guardian in the marriage process is a guardian in one lineage, namely the biological father of his daughter/another ashabah (relative) from the father's side. The purpose of this study is to find out how the Toboino Village community views the guardian's representative in the marriage ceremony and to find out the implications of this view for the guardian's representative in the marriage contract. Based on the analysis carried out, it was concluded that the general public's view of the guardian's representative in the marriage contract is valid because the delegation of guardians is a form of mutual cooperation (mutual help) to people who are less fortunate in several aspects to marry off their daughters. This is due to limited knowledge of religious terms, hesitation in marrying off their daughters, and upholding religious knowledge from the priests more, it is the customary culture of the people of Toboino Village to represent guardians in marriage contracts.